Editorial [ The Contribution of Research to Guide Clinical Practice ] - Belizan, Jose M. (Current Women's Health Reviews, 2006)
An article of this issue is illustrative of research contribution in clinical practice. Progesterone has always been identified as a hormone involved in the initiation of labour due to its role in uterine quiescence, but concomitantly, its use in preventing premature labour was not completely ruled out. Randomised controlled trials have shown that its use can prevent preterm birth in women at risk. Still further research is needed to assess doses, formulations, population recipient, and long term effects before it can be widely recommended for use. Research in this issue is of relevance since preterm birth is a major problem and a challenge in obstetrical care. Another article shows a worrisome situation, that despite the advances in science, many interventions with proven benefit are not implemented in clinical practice and those proven to be of no benefit or deleterious are still used. This is also a major challenge and again, research is needed to search for interventions that could improve the implementation of the best evidences for care. The conjunction of clinical and social scientists is a desired partnership aiming at such interventions. Caution and research based interventions need to be the preference of those providing clinical care. Many external influences and exigencies have attracted the attention of clinicians but they must be cautious in implementing only those interventions which show benefit and lack of deleterious side effects. Moreover, one article of this issue discussed an upcoming unsolved issue in obstetrics i.e., the cord blood banking, which still needs a lot of evaluation and research before its implementation. This subject also has important economic implications and has paved the way for potential inequality in its use. A desired approach evidenced throughout the issue is the analysis in the context of differences related to income and health inequities. An article elucidating on this issue has analysed the use of vaccines during pregnancy under varying circumstances, highlighting that different approaches are needed. Health inequity is an unsolved issue and maternal death is the health indicator delineating the greatest differences between the poor and the rich populations. Regardless many efforts performed at global level, health inequities in provision and the associated results of care are far from improvement and still need consideration. Initiatives and articles focusing on health inequities are highly desirable, promoting the health research community to achieve desirable results.